2017
DOI: 10.31234/osf.io/ufz5w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The perception of emotion in artificial agents

Abstract: Given recent technological developments in robotics, artificial intelligence and virtual reality, it is perhaps unsurprising that the arrival of emotionally expressive and reactive artificial agents is imminent. However, if such agents are to become integrated into our social milieu, it is imperative to establish an understanding of whether and how humans perceive emotion in artificial agents. In this review, we incorporate recent findings from social robotics, virtual reality, psychology, and neuroscience to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Sentiment analysis is also known as opinion or emotion artificial intelligence [ 6 ]. It refers to the use of natural language processing (NLP), text analysis, computational linguistics, and machine learning to systematically analyze people’s written language [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sentiment analysis is also known as opinion or emotion artificial intelligence [ 6 ]. It refers to the use of natural language processing (NLP), text analysis, computational linguistics, and machine learning to systematically analyze people’s written language [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this explanation is not very likely, since the same procedure was used in the study by Van Nieuwenburg et al [6], future studies should consider to directly scenting the robot instead of using 'external' fragrances. Finally, cross-platform generalisability [48,49] could play a role. In a recent evaluation of trust questionnaires most often employed in human-robot interaction, issues of generalisability have been reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Fraune ( 2020 ), we found that people who believed they played against robots showed an even stronger bias towards humanoid robots than humans. As these results are exploratory in nature and the explicit functional role of a robot’s form and shape in the perception and reaction to these agents remain to be understood ( Hortensius, Hekele & Cross, 2018 ), future studies could explore the effect of belief on social cognitive reactions to humanoid and mechanoid robots. Besides the importance of a robot’s appearance, other factors related to social, cognitive, and emotional capabilities of the robot might influence collaboration with a robot.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of Experiments 3 and 4 was to investigate whether individuals show intergroup empathy biases towards robots when they team up with one. We also examined the extent to which our findings might generalise across different robots, an unaddressed issue in the field of social robots ( Cross et al, 2019 ; Henschel et al, 2020 ; Hortensius et al, 2018 ). In Experiment 3, we used the Cozmo robot, a small entertainment robot with a mechanical design, while we used the NAO robot, a humanoid robot often used in HRI research in Experiment 4.…”
Section: Experiments 3 Andmentioning
confidence: 99%